Peningkatan Literasi Kesehatan Mental dan Pemberdayaan Komunitas Desa Sehat Jiwa - Sulastri, Teraika Sri; Elisadevi, Novi; Rostanti, Siti Rohma (Jurnal Ilmiah Psyche, 2025)
Low mental health literacy and strong stigma against individuals with mental disorders remain significant barriers to psychological help-seeking behavior in rural communities. This study aims to develop a community-based intervention model to improve mental health literacy and strengthen local support systems in a village context. An action research approach was applied, involving the active participation of residents from a rural village. Data were collected through in-depth interviews, focused group interviews (FGIs), and participatory observations with 30 participants, including youth, health cadres, community leaders, and local officials.Thematic analysis was conducted through processes of coding, categorization, and contextual interpretation. The findings reveal that mental health literacy in the village community is still limited, marked by a lack of understanding of psychological symptoms, prevailing misconceptions about the causes of mental illness, and continued reliance on non-medical approaches. Interventions such as cadre training, advocacy with village authorities, and the establishment of a youth health post (Posyandu Remaja) contributed meaningfully to enhancing awareness and shifting attitudes toward mental health.This study contributes to the development of a collaborative, community-driven model that can be adapted to similar rural contexts to support mental health promotion efforts. It also extends theoretical perspectives by integrating mental health literacy, ecological systems theory, and participatory approaches as effective strategies for grassroots mental health prevention and care.